Praktek Latihan Kreativitas Menggambar Untuk Remaja Karang Taruna Komplek Bumi Pasundan – Arcamanik Kota Bandung dengan Metode Bahasa Rupa - Tri Haryotedjo; Didit Endriawan; Donny Trihanondo; Teddy Ageng Maulana (ATRAT: Jurnal Seni Rupa, 2025)
This drawing activity aims to improve the drawing skills of Karang Taruna youth in the Bumi Pasundan - Arcamanik Complex, Bandung City, through training based on the Visual Language Method. Visual Language is a method that prioritizes visual understanding as an effective means of communication in fine arts, so that participants can develop creativity and drawing skills in a systematic and structured manner. This activity was designed by a lecturer in Creative Industries, Telkom University, who has competence in the fields of art and design. The method used in this activity consists of theory and practice sessions that cover the basics of drawing, exploration of shape and color, and the application of Visual Language principles in visual works. In addition, participants are also encouraged to understand visual elements such as lines, planes, textures, and composition to improve the quality of their work. A participatory approach is applied in this training, where participants are actively involved in discussions and drawing exercises based on personal experiences and their surroundings. With this activity, it is hoped that Karang Taruna youth in the Bumi Pasundan-Arcamanik Complex will be more motivated to continue developing their drawing skills and utilizing them in various fields, such as illustration, graphic design, or other creative arts. This creative activity is also expected to become a model for similar training in other communities, to encourage the development of local arts and culture.